A Model for the Digital Transformation of Islamic Financial Institutions in Strengthening the Halal Industry Ecosystem in the Era of the 5.0 Industrial Revolution - Basit, Abdul; Knight, Oliver William; Sakti, Reza Arviciena; Zahari, Yudhi Kurniawan (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: Financial institutions are undergoing a transformation toward the digital era in response to the development of fintech and the digital technology revolution.Methods: This study employs a descriptive qualitative approach. The data sources in this study were obtained through library research, namely by reviewing various literature, scientific journals, laws and regulations, financial institution reports, and publications from financial services authorities related to digital banking and green banking in Islamic banking.Results: The findings of this study are that digital transformation, including the use of blockchain, artificial intelligence, big data analytics, and digital financial platforms, has opened new opportunities for Islamic financial institutions to accelerate service processes, expand market reach, and improve operational efficiency—including through digital payment platforms based on Sharia principles. These innovations not only support financial inclusion but also strengthen the integration of the Islamic economy with the real sector, particularly through financing for SMEs and the halal industry, which require faster and more flexible access to financing.Conclusion and suggestion: This study highlights that digital transformation in Islamic financial institutions is essential for strengthening the halal industry ecosystem in the era of Industry 5.0. Therefore, Islamic financial institutions should accelerate digital adoption and enhance human resource capabilities.